2010
DOI: 10.1007/s00213-010-1793-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a functional NOS1 promoter polymorphism on impulsivity is moderated by platelet MAO activity

Abstract: This study supports evidence for higher impulsivity in the NOS1 short/short genotype subjects and further suggests that this is present in the subset of subjects who have close to average platelet MAO activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 39 publications
3
27
0
1
Order By: Relevance
“…Laas and colleagues compared genotype with platelet MAO activity and self-reported impulsivity scores, and reported that short variant NOS1 alleles are related to elevated impulsivity. Furthermore, if short variant individuals have mid range MAO activity, then they have the highest impulsivity scores (Laas et al 2010). Certainly using self-reports of impulsivity is one limitation of this study, but the interaction bears similarity to results in rodents previously described, making the notion of an NO-serotonin interaction in impulsive or aggressive traits among humans plausible.…”
Section: Serotonin-no Interactionssupporting
confidence: 54%
See 1 more Smart Citation
“…Laas and colleagues compared genotype with platelet MAO activity and self-reported impulsivity scores, and reported that short variant NOS1 alleles are related to elevated impulsivity. Furthermore, if short variant individuals have mid range MAO activity, then they have the highest impulsivity scores (Laas et al 2010). Certainly using self-reports of impulsivity is one limitation of this study, but the interaction bears similarity to results in rodents previously described, making the notion of an NO-serotonin interaction in impulsive or aggressive traits among humans plausible.…”
Section: Serotonin-no Interactionssupporting
confidence: 54%
“…Lin and colleagues (Laas et al 2010) applied an optogenetic approach combined with in vivo electrophysiological recording to identify an aggression locus in the mouse hypothalamus. Stimulation with a fiber optic cable of neurons in the VMHvl expressing channelrhodopsin rapidly elicited attack behavior when the male mouse was presented with an intruder, regardless of whether it was a male, female, or castrated male intruder.…”
Section: Advanced Methods and Future Agendamentioning
confidence: 99%
“…In the previous human studies, Reif et al (2009) found an association between a VNTR in the promoter region and many disorders characterized by impulsivity, such as attention deficit hyperactivity disorder, SCZ, and suicide attempt. They also found an association between the same VNTR and self-reported impulsiveness, venturesomeness, and empathy (Retz et al, 2010;Laas et al, 2010;Reif et al, 2011). They further found that the risk variant was associated with altered brain function related to working memory (in an fNIRS study with an N-back task) (Kopf et al, 2011) and attentional control (in both EEG and NIRS studies with the CPT and combined stop-signal and Go/No-Go task) (Kopf et al, 2012;Reif et al, 2006;Reif et al, 2009).…”
Section: Discussionmentioning
confidence: 88%
“…Most of these studies were conducted by Reif et al (2009;2011) and focused on the promoter VNTR. For example, they found that the VNTR had a significant role in impulsive behavior (Retz et al, 2010;Laas et al, 2010;Reif et al, 2011) and mental disorders characterized by impulsive behavior (Reif et al, 2009). They also conducted a series of functional near-infrared spectroscopy (NIRS) studies and found that the VNTR could affect prefrontal activity during a working memory (a letter N-back) task or an attentional control task (combining the stop-signal task with the Go/No-Go task) (Kopf et al, 2012;Kopf et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, recently 3 independent studies of non-clinical samples reported an association between the NOS1 ex1f variable number tandem repeat (VNTR) -functional promoter polymorphismand impulsivity traits measured with different questionnaires [25][26][27] . Hence, it is plausible that NOS1 and NOS3 genes could be implicated in the modulation of impulsive and/or aggressive traits.…”
Section: Discussionmentioning
confidence: 99%